Pemberdayaan Bumdes dalam Mendukung Kewirausahaan di Desa Patongko Kecamatan Tellu Limpoe Kabupaten Sinjai - S, Muh. Rizal; Baharuddin, Aris; Siti Syarifah Wafiqah Wardah; Syarifuddin, Syarifuddin; Seppa, Yusi Irensi (Jurusan Teknik Informatika dan Komputer, 2025)
This community service activity aims to empower Village-Owned Enterprises (BUMDes) in supporting the development of local entrepreneurship in Pattongko Village, Tellu Limpoe District, Sinjai Regency. The main problems faced include the BUMDes manager's low understanding of business management, lack of entrepreneurial skills, and lack of community knowledge regarding local product marketing strategies. To address these issues, this activity was implemented through seminars, training, and intensive mentoring. Seminars presented resource persons from practitioners and academics to provide an understanding of the role of BUMDes in village economic development. Training focused on business planning, financial management, and marketing strategies. Meanwhile, mentoring was conducted to assist participants in developing and implementing the business plan. Evaluation results showed a significant improvement in participants' understanding of entrepreneurial and managerial aspects. This activity also succeeded in generating an entrepreneurial spirit among the village community. It is expected that this activity will be the beginning of the establishment of an independent and sustainable village entrepreneurship ecosystem. Strengthening the capacity of BUMDes through this participatory approach has proven to be effective in encouraging local economic growth based on village potential. Keywords: BUMDes, Pattongko Village, Entrepreneurship, Training, Business Development